2019
DOI: 10.4314/stech.v8i1.1
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of manual control of water hyacinth expansion over the Lake Tana, Ethiopia

Abstract: Water hyacinth is an exotic freshwater weed damaging wetland resources over the Lake Tana basin, Ethiopia. Different measures, including manual labour and harvesting machinery are in use to reduce its damage and expansion. Yet, the invasion of the weed appears expanding its scope across the wetlands of the Lake. This paper presented the study made to identify determinant factors affecting manual control of water hyacinth expansion over the Lake wetlands. It tried to analyse the expansion trend of the water hya… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 13 publications
(27 reference statements)
0
2
0
Order By: Relevance
“…However, the key to its successful control, it has been reported, is the active participation of relevant stakeholders, including the affected locals [ 21 ]. However, a lack of enthusiastic involvement in many instances has led to failures and the re-establishment of the aquatic weed invasion [ 7 , 22 ]. Furthermore, the involvement of locals in water hyacinth management has remained limited to roles at the ground level, for example, monitoring the effect of control strategies implemented by relevant authorities or becoming directly involved in the manual clean-up of water hyacinth [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, the key to its successful control, it has been reported, is the active participation of relevant stakeholders, including the affected locals [ 21 ]. However, a lack of enthusiastic involvement in many instances has led to failures and the re-establishment of the aquatic weed invasion [ 7 , 22 ]. Furthermore, the involvement of locals in water hyacinth management has remained limited to roles at the ground level, for example, monitoring the effect of control strategies implemented by relevant authorities or becoming directly involved in the manual clean-up of water hyacinth [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…WH is considered as fastest growing plant in aquatic ecosystem. For examples, it was reported that the infestation area in Lake Tana (Ethiopia) is up to 50,000 ha, and with an expansion rate of about 13 ha/day ( Dersseh et al, 2019 ; Yitbarek et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%